2009
DOI: 10.1096/fj.09-134643
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory therapy by intravenous delivery of non‐heparan sulfate‐binding CXCL12

Abstract: Interaction between chemokines and heparan sulfate (HS) is essential for leukocyte recruitment during inflammation. Previous studies have shown that a non-HS-binding mutant form of the inflammatory chemokine CCL7 can block inflammation produced by wild-type chemokines. This study examined the anti-inflammatory mechanism of a non-HS-binding mutant of the homeostatic chemokine CXCL12. Initial experiments demonstrated that mutant CXCL12 was an effective CXCR4 agonist. However, this mutant chemokine failed to prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 41 publications
3
66
0
Order By: Relevance
“…As expected (19,21,(45)(46)(47) Next, we studied the effects of the CXCR4 and ACKR3 ligands that did not influence normal blood pressure in a hemorrhagic shock model. This model consisted of 30 min hemorrhage to a mean arterial blood pressure (MAP) of 30 mmHg followed by crystalloid fluid resuscitation to a MAP of 70 mmHg.…”
Section: Cxcr4 and Ackr3 Ligands Modulate Hemodynamics And Blood Presmentioning
confidence: 78%
“…As expected (19,21,(45)(46)(47) Next, we studied the effects of the CXCR4 and ACKR3 ligands that did not influence normal blood pressure in a hemorrhagic shock model. This model consisted of 30 min hemorrhage to a mean arterial blood pressure (MAP) of 30 mmHg followed by crystalloid fluid resuscitation to a MAP of 70 mmHg.…”
Section: Cxcr4 and Ackr3 Ligands Modulate Hemodynamics And Blood Presmentioning
confidence: 78%
“…[11][12][13][14][15] K24S and K25S point mutations were introduced in the critical HSbinding domain (encoded in the second exon) shared by the 3 CXCL12 isoforms ( Figure IIA in the online-only Data Supplement). Furthermore, a nonsense amber mutation was introduced in the fourth exon to prevent the translation of the distinctive 30 last Aa of the highly cationic C-ter domain of CXCL12␥ ( Figure IA in the online-only Data Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…12 We reported previously that neutralization of the K24H25L26K27 cationic charge (K24S and K27S substitutions) is sufficient to drastically reduce binding to HS and complexing of CXCL12␣ with either immobilized heparin or HS. [11][12][13][14] Similarly, O'Boyle et al 15 recently reported that combined K24S and K27S in CXCL12␤ are sufficient to impede HS binding of this isoform on the apical surface of endothelial cells and promote a dramatic blood and delayed clearance compared with the wild-type (WT) counterpart. To abrogate HS binding of CXCL12␥, the mutation of K24H25L26K27 combined with the C-ter 4 -overlapping BBXB motifs is required.…”
Section: Clinical Perspective On P 1895mentioning
confidence: 99%
See 2 more Smart Citations